1997
DOI: 10.1111/j.1360-0443.1997.tb03200.x
|View full text |Cite
|
Sign up to set email alerts
|

Solitary drinking: a risk factor for alcohol‐related problems?

Abstract: This paper investigates whether solitary drinking is a risk factor for alcohol-related problems using data from a general population of drinkers in Montréal, Canada. Three indicators of solitary drinking were used: (1) having had a drink alone; (2) frequency of solitary drinking; and (3) having had five drinks or more in a solitary setting. Among the 2015 respondent drinkers of a telephone survey, 31% reported drinking alone, of whom 27% did so more than once a week, and 17% had had five drinks or more alone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…Drinking in non-normative contexts is conceptualized as particularly harmful (Bourgault & Demers, 1997). Solitary drinkers report earlier onset of regular alcohol use, lower motivation to reduce excessive use, and more alcohol-related problems relative to primarily social drinkers (Christiansen et al, 2002;Gonzalez et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking in non-normative contexts is conceptualized as particularly harmful (Bourgault & Demers, 1997). Solitary drinkers report earlier onset of regular alcohol use, lower motivation to reduce excessive use, and more alcohol-related problems relative to primarily social drinkers (Christiansen et al, 2002;Gonzalez et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…At university events, peers encourage each other to use alcohol heavily (Johnston, O'Malley, & Bachman, 2001). Without social companions to facilitate heavy drinking (Bourgault & Demers, 1997), solitary drinkers may be able to limit their use to some degree, but given their coping reasons for use, they remain at risk for alcoholrelated problems. Moreover, there was a lack of association between depressive symptoms and intimate drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Religion and identity (Neff & Husaini, 1985); solitary drinking (Bourgault & Demers, 1997), young people and designer drinks Macintosh et al, 1997) and identity and the pub (Smith, 1983) have also been pertinent topics studied in local, regional or national contexts.…”
Section: Alcohol Studies and Geographymentioning
confidence: 98%
“…Coping motives were also associated with binge drinking. Concerning drinking alone, Bourgault and Demers [48] found that adults drinking alone were at increased risk for alcohol-related problems only if large quantities were consumed. Gonzalez et al [49] simultaneously studied these two aspects in a sample of young adults (aged 18-20 years), showing that drinking to cope was associated with drinking heavily while being alone.…”
Section: Discussionmentioning
confidence: 99%